The Effect of a Short-Term Detraining Period on Neuromuscular Performance in Elite U18 Male Basketball Players - Nieto-Acevedo, Raúl (Wolters Kluwer, 2025)
Nieto-Acevedo, R, García-Sánchez, C, Romero-Moraleda, B, Varela, D, and Cabarkapa, D. The effect of a short-term detraining period on neuromuscular performance in elite U18 male basketball players. J Strength Cond Res 39(11): e1305-e1312, 2025-The purpose of this study was to investigate the effect of 14 days of detraining (complete cessation in training) on neuromuscular performance in 10 elite basketball male players younger than 18 years. A descriptive longitudinal design was used, the athletes were evaluated using force plates on 3 separate occasions (i.e., 14 days prior, 24 hours after, and 14 days after). Neuromuscular performance was evaluated using isometric mid-thigh pull (IMTP), countermovement vertical jump (CMJ), and 20-meter sprint tests. Test-retest reliability was established in 2 preliminary sessions. Prepost detraining differences were analyzed using paired t tests. No significant differences pre- and postdetraining were observed in IMTP ( p > 0.05; effect size [ES] = 0.0-0.13), and 20-meter sprint ( p = 0.07, ES = 0.69). However, CMJ performance exhibited significant increases in reactive strength index-modified, peak and mean propulsive force, peak and mean braking force, and braking net impulse ( p < 0.001-0.017; ES = 0.50-0.73), alongside reductions in propulsive phase duration and time to take off ( p < 0.001; ES = 0.49 and 0.019; ES = 0.88, respectively). Despite 14 days of detraining, IMTP and sprint performance remained stable, while some braking and propulsive metrics of CMJ demonstrated significant positive adaptations. Overall, these findings suggest that short-term detraining does not impair maximal force production or sprint ability and induces alterations in jump mechanics, particularly within braking and propulsive phases of CMJ. Coaches should consider the observed neuromuscular changes-particularly the reduction in take-off time despite stable jump height-when planning training resumption strategies. Emphasizing the restoration of explosive strength and reactivation of movement patterns early in the return-to-training phase may help mitigate potential performance fluctuations after short-term detraining.